Interdisiplinary Programs in an University Setting - Kast, Fremont E.; Rosenzweig, James E.; Stockman, John W. (Academy of Management Journal, 1970)
This paper focuses upon the organizational and administrative problems associated with interdisciplinary research programs?using an illustrative case, the Ceramic Materials Research Program at the University of Washington. The investigation suggests that there are many organizational constraints operating to forestall pure interdisciplinary research. During the early years of the research program there were numerous administrative and organizational difficulties. There was a learning-adapting process in the development of a viable program; however, an effective structure did evolve which provided for overlapping group membership on various committees which linked the participants together. A program-type organization was superimposed upon the existing university structure. The research findings suggest that interdisciplinary research often requires that a hybrid form of organization structure be developed to compensate for obstacles inherent in the university setting. A flexible ?free-form? program structure allows more responsive adaptation to change and minimizes the barriers of departmental lines.